Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Fracture propagation and stability of ice shelves governed by ice shelf heterogeneity - Borstad, Chris; McGrath, Daniel; Pope, Allen (Geophysical Research Letters, 2017)
Tabular iceberg calving and ice shelf retreat occurs after full-thickness fractures, known as rifts, propagate across an ice shelf. A quickly evolving rift signals a threat to the stability of Larsen C, the Antarctic Peninsula's largest ice shelf. Here we reveal the influence of ice shelf heterogeneity on the growth of this rift, with implications that challenge existing notions of ice shelf stability. Most of the rift extension has occurred in bursts after overcoming the resistance of suture zones that bind together neighboring glacier inflows. We model the stresses in the ice shelf to determine potential rift trajectories. Calving perturbations to ice flow will likely reach the grounding line. The stability of Larsen C may hinge on a single suture zone that stabilizes numerous upstream rifts. Elevated fracture toughness of suture zones may be the most important property that allows ice shelves to modulate Antarctica's contribution to sea level rise.
Keywords: Antarktis; geofysikk; glasiologi; havnivåstigning; is; isberg; isbrem; isfjell; isshelf; kalv; kalving

Tsunami and infragravity waves impacting Antarctic ice shelves - Bromirski, Peter D; Chen, Zhao; Stephen, Ralph A; Gerstoft, Peter; Arcas, Diego; Diez, Anja; Aster, Richard C; Wiens, Douglas A; Nyblade, Andrew Arnold (Journal of Geophysical Research: Oceans, 2017)
The responses of the Ross Ice Shelf (RIS) to the 16 September 2015 8.3 (Mw) Chilean earthquake tsunami (>75 s period) and to oceanic infragravity (IG) waves (50–300 s period) were recorded by a broadband seismic array deployed on the RIS from November 2014 to November 2016. Here we show that tsunami and IG-generated signals within the RIS propagate at gravity wave speeds (∼70 m/s) as water-ice coupled flexural-gravity waves. IG band signals show measureable attenuation away from the shelf front. The response of the RIS to Chilean tsunami arrivals is compared with modeled tsunami forcing to assess ice shelf flexural-gravity wave excitation by very long period (VLP; >300 s) gravity waves. Displacements across the RIS are affected by gravity wave incident direction, bathymetry under and north of the shelf, and water layer and ice shelf thicknesses. Horizontal displacements are typically about 10 times larger than vertical displacements, producing dynamical extensional motions that may facilitate expansion of existing fractures. VLP excitation is continuously observed throughout the year, with horizontal displacements highest during the austral winter with amplitudes exceeding 20 cm. Because VLP flexural-gravity waves exhibit no discernable attenuation, this energy must propagate to the grounding zone. Both IG and VLP band flexural-gravity waves excite mechanical perturbations of the RIS that likely promote tabular iceberg calving, consequently affecting ice shelf evolution. Understanding these ocean-excited mechanical interactions is important to determine their effect on ice shelf stability to reduce uncertainty in the magnitude and rate of global sea level rise.
Keywords: Sørishavet; brehylle; havnivåstigning; is; isbrem; isshelf; kalv; kalving; oseanografi; seismologi

Antarktis-isen: større og dypere - Bjermeland, Monica (Klima: norsk magasin for klimaforskning, 2013)
De siste tiårene har isen i Antarktis økt litt i utbredelse. Men ikke fordi det er blitt kaldere der.
Keywords: Antarktis; Sørishavet; glasiologi; havis; is; klima

Mindre snø enn forventet i Antarktis - Anschütz, Helgard; Isaksson, Elisabeth (Klima: norsk magasin for klimaforskning, 2010)
Keywords: Dronning Maud Land; glasiologi; is; klima; snø

Snow and Ice Studies By Thematic Mapper and Multispectral Scanner Landsat Images - Orheim, Olav; Lucchitta, Baerbel K (Annals of Glaciology, 1987)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; is; satellittbilder; snø

Field experiments on Antarctic tabular icebergs - Kristensen, Monica; Orheim, Olav; Wadhams, Peter (Polar Record, 1981)
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi; is; isfjell; isshelf; kalv; kalving

Measurements of oscillations and flexure of icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; havis; is; isbreer

Measurements of the radiation temperature of Antarctic icebergs and the surrounding surface water - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; ekspedisjoner; glasiologi; havis; is; isbreer

Studies of icebergs, ice fronts and ice walls using side-scanning sonar - Klepsvik, John O; Fossum, Bjørn A (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; NARE 1978/79; ekspedisjoner; forskning; glasiologi; is; isberg; isfjell; isfront; morfologi; snø

The filtering effect of snow - Gjessing, Yngvar (International Association of Hydrological Sciences Publication, 1977)
Keywords: Dronning Maud Land; analyser; hydrologi; is; kjemisk; snø